Photofragmentation studies of metal ion-molecule complexes and metal oxides - Iskra, A (2017)
Gas phase metal-containing complexes provide suitable systems in which to study fundamental binding motifs between a metal ion and molecules in the absence of any solvent, support or competing charge effects. In this thesis, metal-containing species are explored experimentally using infrared resonance enhanced photodissociation (IR-REPD) spectroscopy and velocity map imaging (VMI). The experimental results are further interpreted with the aid of spectral simulations based on density functional theory (DFT). These are the first studies reported using a newly built IR-REPD spectrometer equipped with a purpose-built laser ablation source to allow for the study of single metal ion-molecule complexes. The laser ablation source is shown to efficiently produce various complexes including Rh+(CO2)n, VO2+(N2O)n and Au+(CH4)n and the IR-REPD spectrometer has been characterised against a well-studied system of V+(CO2)n complexes. In order to record the IR-REPD spectra for small metal ion-molecule complexes, an argon atom is employed as the inert messenger. A combined IR-REPD spectroscopy and DFT investigation of M+(CO2)n complexes (where M = Co+, Rh+ and Ir+) reveals a common [M+(CO2)2] core structure for all three considered metal ions. Additional ligands, which are not directly bound to the central metal ion, experience lower perturbation as evident in the reduced blue-shift for the ligand in the outer coordination shells. A further IR-REPD/DFT study involving CO2 complexation around NbO2+ and TaO2+ ions reveals a strongly-bound core of four CO2 ligands around the MO2+ ion (M = Nb, Ta). A significant increase in the intermolecular bond distances for the second coordination sphere ligands coincides with a decrease in the calculated binding energies. Velocity map imaging is employed to explore the rich photodissociation dynamics of VO in the vicinity of C4Σ- - X4Σ-(v',0) vibronic transitions in VO. The final quantum state distribution was observed to be strongly dependent on the intermediate vibronic state of VO via which the dissociation threshold is reached. This work provides a refined value for the VO dissociation energy of D0(VO) = 53190 ± 261 cm-1 in excellent agreement with available literature.